The Semiotic Analysis of OTOP Advertisement Poster 2010-2023 Paradigm of Thailand Local Image Development - Maneenetra, Piti (Asia Social Issues, 2025)
The article investigated the OTOP Advertisement Poster (OAP) within the period of 2010 – 2023 as the local revolution phenomena in Thailand by semiotics analysis. To address the first research question: What factors in OTOP public policy influence media design communication targeted at audiences? and the second research question: How is the value of Thai locality communicated through the OTOP image? From the paradigm of public sector of local image communication, many clues can appear in media that cannot specify visual concepts of certain identities, and design characteristics are broadly mere ideations. Questioning OTOP brand image, semiotic framework select sample from different 3 main events which can be filtrated by 59 samples from 410 namely OTOP City (OC), OTOP Midyear (OMY) and OTOP Silpachep (OSP). The findings revealed 11 signifier categories, which researchers identified as controllable through 6 internal significations, namely; 1) Wisdom-Identity, 2) Spatial-Cognition, 3) Femininity-Ideal, 4) Geographical-Product, 5) Traditional-Monarchy, 6) Modernism-Innovation and external signification 7) Tangible-Value, 8) Fortune-Auspicious, 9) Nourishment, 10) Population, 11) Period Time-Festive. Social reproduction of design language on OAP created the norms consisting 5 different parts listed as: i) Femininity ideal, ii) Realm of decoration, iii) Western signifying the perception of modernity, iv) The researchers view locality as a political reflection and associate it with v) beliefs rooted in tradition and culture. OAP criticism is the social discourse of Thailand’s local image design development. Policymakers should consider decentralizing and reorganizing according to the 4D model to lay the foundation of sustainable local development.